Levels of salinity and fertigation management on the characteristics of the eggplant when grown in a protected environment - Silva, Everaldo (2012)
The objective was to study the effects of different levels of soil salinity on the phenological variables and production of the eggplant when grown in pots in a protected environment. The study was carried out at the experimental site of the Department of Biosystems Engineering ESALQ/USP in Piracicaba, São Paulo. The treatments consisted of a combination of two factors: six initial levels of soil salinity (S1 = 1.3, S2 = 2.4, S3 = 3.6, S4 = 4.5, S5 = 5.6 and S6 = 6.4 dS m-1) and two fertigation management: with the electrical conductivity of the soil solution being controlled (M1) and traditional (M2), following the absorption curve of nutrients from the culture. The statistical design adopted was a randomized complete-block design with four replications, arranged in a 6 x 2 factorial. The results showed that the levels of soil salinity directly affected the variables of dry-matter production, fruit production and leaf-area index of the plants. It was found that the average reduction in yield of the eggplant crop in a greenhouse, was approximately 8.65% for an increase of 1 dS m-1 in the salinity of the soil above the threshold salinity of 1.71 dS m-1.